Paciente neonato con ictericia por incompatibilidad feto materno por el grupo sanguíneo ABO - Tomalà Bravo, Génesis Noemi (2019)
The present work leads to the creation of a clinical case with the neonate theme with jaundice due to maternal fetus incompatibility by the ABO blood group. This case was presented in the Sacred Heart Hospital of Jesus, place of origin, City of Quevedo, parish, October 7, in the area of Neonatology. For this case, a diagnosis methodology was made where the patient's clinical history is known, the presumptive, differential, definitive, and nursing data formulation, follow-up and observations. In addition, the theoretical framework is deepened where information about neonatal jaundice is investigated, where different authors tell us. Neonatal jaundice remains a frequent pathological condition in the newborn and one of the main causes of hospital admission during the first week of life. Is the jaundice that occurs in the first 24 hours, is accompanied by other symptoms, bilirubin increases more 5mg / dl / day, direct bilirubin is greater than 2mg / dl or lasts more than a week in the term newborn or more than two weeks in the preterm. ABO incompatibility is an immune reaction that occurs in the body when two blood samples of different and incompatible ABO types are mixed. It is the most frequent of the fetal blood incompatibilities. It occurs in mothers group O and fetuses group A or B.